A critical review of analytical methods for quantification of rivaroxaban in biological samples and pharmaceutical formulations - Ajitha Azhakesan, Kishore Kumar Pasupuletti, Narendra Pentu (Journal of Applied Pharmaceutical Science, 2025)
Rivaroxaban (RXN) is a direct oral anticoagulant (direct inhibitor of factor Xa) used in the treatment of atrial fibrillation to reduce the risk of stroke caused by clot, periphery, and coronary heart disease. The foremost goal of the pharmaceutical drug is to exert its therapeutic action and cure the disease. Considering the therapeutic importance of RXN, this review focuses on the various spectrophotometric (UV) and chromatographic methods (thin-layer chromatography, high-performance thin-layer chromatography, high-performance liquid chromatography, ultra-performance liquid chromatography, liquid chromatography-tandem mass spectrometry, ultra-performance liquid chromatography-tandem mass spectrometry) available for the quality control and pharmacokinetic studies of RXN. The analytical methods published provide an overview of the various instrumental techniques that establishes the identity, quality, and purity of RXN. Stability-indicating methods anticipate the degradation products (DPs)/pathways of RXN which would help researchers to elucidate the structure of DP. The proposed review explores the greenness profiles of the reported analytical methods (2010–2024) based on the National Environmental Method Index in view of sustainable development goals 2030. The published bioanalytical methods provide a roadmap for potential researchers in developing more robust, efficient, and eco-friendly methods incorporating sorbent-based microextraction techniques to enhance biomedical research. Also, researchers incorporate analytical quality-based design (AQbD) which augments the quality and shrinks the out-of-trend and out-of-specification to expedite the regulatory flexibility in the analytical method. Overall this review illuminates the future canvassers to develop greener methods using eco-friendly solvents incorporating AQbD for the determination of RXN in biological fluids and drug products.
Keywords: Rivaroxaban, AQbD, UV, HPLC, UPLC, biological fluids